Publicaciones de José Enrique Martínez Fernández - Álvarez Méndez, Natalia; Martínez Cantón, Clara Isabel; Trabado Cabado, José Manuel (Tropelías: Review of Literary Theory and Comparative Literature, 2017)
Publicaciones de José Enrique Martínez Fernández